Urinary Bladder Cancer in Young Adult - A Rare Case Report: Painless Haematuria to be Presenting Symptoms (Bangladesh Journal of Urology, 2022)
Bladder urothelial carcinoma (UC) it is the fifth most prevalent carcinoma in humans, nevertheless in children and young adults it’s very rare. It usually occurs in older adults. We present a 4-year-old boy with a painful microscopic hematuria. Ultrasound revealed a irregular lobulated mass lesion in right supero-lateral wall of urinary bladder and a thick bond extending towards left lateral wall which was confirmed by computed tomography (CT). The first biopsy was compatible with urothelial papilloma. Transurethral resection of the bladder tumor (TURBT) was performed and histopathology showed urothelial neoplasm of low malignant potential (PULMP).Bangladesh J. Urol. 2021; 24(2): 229-231